Quality and Distribution of Lead and Cadmium in Underground Water of Kashmir - Aslam Mirza, M.; Khuhawar, M.Y.; Arain, Rafee (Asian Journal of Chemistry, 2010)
Maintenance of ecosystem based on the biogeochemistry of Kashmir lying at the foothills of Himalayas is not just crucial for its inhabitants but also for down stream Indus river system made up mainly of snowmelt, spring ooze, lake aqua stock of Kashmir. Through an appropriate sampling strategy an area of 13297 Km2 with a population density of 330 persons/Km2 was studied. 40 Wells, 20 hand pumps and 30 major springs were selected for measuring 30 in situ and laboratory water quality parameters over a period of 4 years providing base line data on underground water source of Kashmir. The study also encompasses seasonal variations over hydrological cycles and effect of anthropogenic activity. The results indicate the presence of major nutrients (Na+, K+, Ca2+, Mg2+) within WHO thresholds and of trace metal presence of Fe2+, Cu2+, Zn2+, Ni2+, Cd2+, Pb2+ Co2+; Cd and Pb show elevated amounts irrespective of seasonal changes or dilution by precipitation. This is a cause of concern endangering the fragile ecosystem of this area. Human activity is also aggravating it. A remedy of this problem could be the recourse to a proper and extended study of the composition of soil and biological interactions per se responsible for releasing these contaminants to the hydro cycle.